SAT0078 SAFETY OF LOW DOSE METHOTREXATE (MTX) IN HUMAN IMMUNODEFICIENCY VIRUS (HIV) INFECTION. (2nd June 2020) - Gunay, A.; Davidson, A.; Colmegna, I.; Lacaille, D.; Loewen, H.; Meltzer, M.; Mengistu, Y.; Scuccimarri, R.; Yirsaw, Z.; Bernatsky, S.; Hitchon, C.
Abstract : Background: Increased awareness of the efficacy of MTX in rheumatic disease is leading to more MTX use in patients from HIV endemic areas. While HIV related immunosuppression may contribute to improvement of some rheumatic diseases, immune reconstitution from highly active antiretroviral therapy (HAART) may lead to exacerbation or presentation of autoimmune disorders for which MTX therapy may be warranted. Most management guidelines for rheumatic disease do not address MTX use in the context of HIV. Objectives: To systematically review the published literature on the safety of using MTX ≤30 mg per week in HIV. Methods: We searched CINAHL, Embase, Global, MEDLINE and World of Science databases (Jan 1990 to May 2018) for terms including 'methotrexate' and 'human immunodeficiency virus'. We also searched citations from review articles. Titles, abstracts or full manuscripts were screened independently by 2 reviewers to identify studies reporting HIV in patients taking MTX. Study quality was assessed using the McGill Mixed Methods Appraisal Tool (MMAT). Data was extracted on MTX and HIV adverse events (MTX toxicity, HIV viral load, CD4 count). Descriptive summaries are presented for studies providing outcomes in patients taking MTX ≤30 mg per week. Results: After removing duplicates and studies not meeting criteria or not providing sufficient information, 42 of the 2714 identified reports were included (1 clinical trial, 2 cohort, 1 cross-sectional study, 38 case reports/case series). Most reports (81%) originated from USA or Europe. Study quality was generally good with most studies fulfilling 50-100% of MMAT criteria. The randomized controlled trial (USA) assessing MTX on atherosclerotic disease in HIV showed that adverse events were more common in MTX versus placebo (12.8% vs 5.6%, p non-inferiority <0.05) and included infection, transient CD4 and CD8 drop, pulmonary toxicity, and death (1 attributed to MTX/HIV, 1 unrelated). One cohort study (South Africa) reported 43 RA patients on MTX who acquired HIV. In this cohort, RA generally improved despite only 5 individuals continuing MTX. No data on MTX adverse event rates was reported. One cohort study (USA) reported 13 HIV patients with myositis. One received MTX (with other immunosuppression) without MTX adverse effects but died due to AIDS. A cross-sectional study (France) of 43 HIV pts with autoimmune disease reported one patient on MTX (and other immunosuppression) developed an adverse event (cytopenia) compared to 5/33 patients not on MTX (cytopenia). The 38 case reports/series described 54 individuals with HIV receiving MTX. Of these studies, 27 (describing 42 subjects) reported on MTX adverse events and 35 (describing 46 subjects) reported on HIV adverse events. MTX adverse events developed in 29 subjects (hematologic 13, renal/hepatic 1, opportunistic infections 10, other events 2). HIV adverse events were noted in 23 subjects (Kaposi's sarcoma 4, CD4 decrease 16, HIV viral titer increase 4). Five deaths were reported (2 infection, 1 infection and wasting, 2 HIV related deaths). Most subjects also received corticosteroids or other immunosuppressants including biologics. Conclusion: There remains limited data on the safety of low dose MTX in HIV. Surveillance for HIV is warranted for individuals on MTX who are at risk for acquiring HIV. Caution and careful monitoring for MTX toxicity, opportunistic infections and HIV state is suggested if MTX is used in the setting of HIV particularly if combined with other immunosuppression. References: [1] Clin Infectious Disease 2019:68 [2] J Rheumatology 2014:41 [3] Arthritis and Rheumatism 2003:49 [4] Medicine 2017:96 Acknowledgments: Funding from International League Against Rheumatism McGill University Global Health Scholar Awards Disclosure of Interests: Alize Gunay: None declared, Anna Davidson: None declared, Ines Colmegna: None declared, Diane Lacaille: None declared, Hal Loewen: None declared, Michele Meltzer: None declared, Yewondwossen Mengistu: None declared, Rosie Scuccimarri: None declared, Zenebe Yirsaw: None declared, Sasha Bernatsky: None declared, Carol Hitchon Grant/research support from: UCB Canada; Pfizer Canada